Strategi Guru Pendidikan Agama Islam dalam Peningkatan Motivasi Belajar Siswa di SMK Al-Kautsar Grogol Jombang - Berlian, Intan; Masrufa, Binti (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
This study aims 1. To describe the strategy of Islamic religious education teachers in increasing student motivation at SMK Al-Kautsar Grogol Jombang. 2. To describe students' learning motivation at SMK Al-Kautsar Grogol Jombang. 3. To describe the supporting and inhibiting factors of PAI teachers in increasing student motivation at SMK Al-Kautsar Grogol Jombang. The method used is a qualitative method with a qualitative descriptive design with data collection through observation, interviews, and documentation. Furthermore, analysis was carried out and used qualitative descriptive. The results showed that the success of PAI teachers in increasing student motivation at SMK Al-Kautsar Grogol Jombang was good enough but needed to be improved. This can be seen from the fact that there are still students who fall asleep during learning and do not want to take part in PAI learning properly and cannot practice the recommendations contained in PAI learning. Therefore, PAI teachers here use several strategies such as combining various methods, giving grades, holding competitions, competition for giving praise and giving punishments that aim to increase student learning motivation.